2001
DOI: 10.1007/s002130000627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketoconazole on the acquisition of intravenous cocaine self-administration under different feeding conditions in rats

Abstract: These results extended previous findings of the suppressant effects of ketoconazole on cocaine-reinforced responding in rats to the acquisition of cocaine self-administration using food restriction as a stressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 49 publications
1
40
1
Order By: Relevance
“…A number of studies have established that exposure to a variety of stressors, including uncontrollable EFS, facilitates the acquisition of cocaine SA by rats (see eg Goeders and Guerin, 1994;Haney et al, 1995;Miczek and Mutschler, 1996;Ramsey and Van Ree, 1993;Campbell and Carroll, 2001;Kosten et al, 2000;Schenk et al, 1987) and reinstates extinguished cocaine-seeking behavior (Erb et al, 1996;Ahmed and Koob, 1997;Mantsch and Goeders, 1999a;Shalev et al, 2003). Our finding that daily EFS delivered across a period of ongoing SA escalates cocaine intake after acquisition has occurred extends these findings and is consistent with reports that food deprivation elevates postacquisition cocaine SA (Carroll, 1985) and that repeated social-defeat stress extends the duration of SA and increases the cumulative amount of cocaine self-administered by rats during unlimited-access 'binges' (Covington and Miczek, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have established that exposure to a variety of stressors, including uncontrollable EFS, facilitates the acquisition of cocaine SA by rats (see eg Goeders and Guerin, 1994;Haney et al, 1995;Miczek and Mutschler, 1996;Ramsey and Van Ree, 1993;Campbell and Carroll, 2001;Kosten et al, 2000;Schenk et al, 1987) and reinstates extinguished cocaine-seeking behavior (Erb et al, 1996;Ahmed and Koob, 1997;Mantsch and Goeders, 1999a;Shalev et al, 2003). Our finding that daily EFS delivered across a period of ongoing SA escalates cocaine intake after acquisition has occurred extends these findings and is consistent with reports that food deprivation elevates postacquisition cocaine SA (Carroll, 1985) and that repeated social-defeat stress extends the duration of SA and increases the cumulative amount of cocaine self-administered by rats during unlimited-access 'binges' (Covington and Miczek, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have demonstrated that stressors facilitate the acquisition of cocaine SA (see eg Goeders and Guerin, 1994;Haney et al, 1995;Miczek and Mutschler, 1996;Ramsey and Van Ree, 1993;Campbell and Carroll, 2001;Kosten et al, 2000;Schenk et al, 1987) and reinstate extinguished cocaine-seeking behavior (Erb et al, 1996;Ahmed and Koob, 1997;Mantsch and Goeders, 1999a;Shalev et al, 2003). By contrast, the ability of stress to produce escalating patterns of cocaine SA has not been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, daily food was restricted to 18 g of standard rat chow in order to maintain animals at approximately 85% of the mean body weight of non-food-deprived littermates (not participating in the study). Moderate food restriction has been shown consistently to accelerate cocaine acquisition (Campbell and Carroll, 2001), and the procedure is recommended for autoshaping acquisition studies. Uncontaminated water was available ad libitum throughout the study.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…Subsequently, daily food was restricted to 18 g of standard rat chow in order to maintain animals at approximately 85% of their mean free-feeding body weight. This food-restriction regimen is similar to that used in other laboratories (e.g., Campbell and Carroll, 2001). Moderate food restriction consistently has been shown to accelerate methamphetamine acquisition (Roth and Carroll, 2004), and the procedure is recommended for autoshaping acquisition studies.…”
Section: Surgicalmentioning
confidence: 97%
“…It has been argued that the rate of acquisition of drug selfadministration may serve as a predictor of later drug-taking behavior, possibly influencing the transition from drug use to addiction (refer to Rocha et al, 2005). Accordingly, in Experiment 1 an acquisition paradigm developed by Carroll and associates (Campbell and Carroll, 2001;Carroll and Lac, 1997) was employed to train lead-exposed and control animals to press a lever for a methamphetamine-reinforcement in a consistent manner, with minimal intrusions. In this preparation, Pavlovian conditioning is first used to shape behavior, then operant conditioning is tested in order to measure rate of methamphetamine acquisition in the animals.…”
Section: Introductionmentioning
confidence: 99%